Diagnostic utility of lung echography for congestive heart failure performed by junior resident doctors. (17th August 2022) - Nagaharu, Keiki; Tsumura, Natsumi; Itoh, Toshiyuki; Murata, Tetsuya
Abstract: Background: Dyspnea is a high priority symptom in the emergency department, with heart failure (HF) as one of its leading causes. Recently, the "comet tail sign (CTS), " a pulmonary ultrasonographic sign, has been proposed as an efficacious tool for detecting pulmonary edema. However, to the best of our knowledge, there have been no published data regarding its utility when performed by non‐experts, including junior residents. Methods: Between September 2017 and December 2018, patients with dyspnea, who were admitted to the ER, were enrolled. CTS was evaluated by junior residents at the ER. All patients were evaluated by cardiologists independently, and clinical HF was defined as requiring pharmacological intervention by a cardiologist. At the end of this study, we investigated the results of CTS, laboratory data, and available radiological images. Results: A total of 95 patients were enrolled in the current study, wherein 42 patients were treated by cardiologists as those with clinical HF. Our results showed that CTS could identify clinical HF with a sensitivity of 71.4% and a specificity of 81.1%. The sensitivity of CTS against brain natriuretic peptide (BNP) (cut‐off value, 100 pg/ml) was calculated at 92.5%. Furthermore, when evaluated together with peripheral edema, CTS identified clinical HF with a sensitivity of 96%. False positives for CTS included bilateral pneumonia, hypoalbuminemia, and interstitial pneumonitis. Conclusions: Our results indicate that CTS is a simple and effective tool for the use of non‐experts, including junior residents. Abstract : CTS is an easy and effective tool for non‐experts, including junior residents, to use.